The genes coding for the cardiac muscle actin, the skeletal muscle actin and the cytoplasmic beta-actin are located on three different mouse chromosomes. - Czosnek, H (1983)
The actins are a group of highly conserved proteins encoded by a multigene family. We have previously reported that the skeletal muscle actin gene is located on mouse chromosome 3, together with several other unidentified actin DNA sequences. We show here that the gene coding for the cardiac muscle actin, which is closely related to the skeletal muscle actin (1.1% amino acid replacements), is located on mouse chromosome 17. The gene coding for the cytoplasmic beta-actin is located on mouse chromosome 5. Thus, these three actin genes are located on three different chromosomes.